G141(P) Identifying inflammatory bowel disease in cases with no gastrointestinal symptoms at presentation. (May 2019) - Shepherd, K; Kilonback, A; Shivamurthy, V; Wilkinson, N
Abstract : Case 1: A 16-year-old male presented with limp and marked hip restriction had an insidious onset with no trigger, infectious contact or gastrointestinal symptoms. He was otherwise systemically well. His blood work up was unremarkable, HLAB27 screen was negative and MRI confirmed a large right hip joint effusion. All cultures including a hip joint aspirate had no growth. He was diagnosed with coxitis and started on oral prednisolone and etanercept. Six weeks into etanercept treatment it was stopped due to recurrent perianal abscesses. A biopsy had histopathological findings consistent with Crohn's disease. The patient received exclusive enteral nutrition for induction and azathioprine for maintenance treatment of Crohn's. On stopping the etanercept his arthritis flared and he is now being considered for another TNFα inhibitor. Case 2: An 11-year-old female presented to her local hospital with severe bilateral hip pain and restriction following a six-week history of deteriorating pain and stiffness. She had no systemic features, gastrointestinal symptoms or preceding infection or trauma. On examination, she had restricted range of movement in both hips and reduced power in left hip extension, abduction and flexion. Blood work revealed a CRP of 103 mg/L with a reactive blood film. HLA-B27 screen was negative. All cultures including a hip joint aspirate had no growth. MRI demonstrated bilateral hip effusions and inflammatory changes that was most compatible with chondrolysis rather than frank synovitis. She was transferred to a tertiary centre for further work up, where a whole-body MRI did not find any other focus. Bone marrow aspirate was unremarkable. She was unresponsive to a two week trial of oral steroids. During this time a stool calprotectin returned elevated at 950 ug/g with a gastroenterology review indicating a high likelihood of inflammatory bowel disease. Our plan after completion of endoscopy is to use a TNFα inhibitor. These unusual cases of primary coxitis recommend considering inflammatory bowel disease in the differential at presentation. Faecal calprotectin presents a simple non-invasive screening test for these conditions.